Detection of herpesvirus DNA by the polymerase chain reaction (PCR) in vitreous samples from patients with necrotising retinitis - Nogueira, M (2001)
Aims—Viral uveitis and retinitis, usually caused by herpesviruses, are common in immunosuppressed patients. The diagnosis of viral anterior uveitis and retinitis is usually clinical. The polymerase chain reaction (PCR) has been used for the diagnosis of some viral infections, especially those caused by herpesviruses. This paper reports the use of PCR in the diagnosis of viral retinitis in vitreous samples from Brazilian patients. Methods—PCR was used for the diagnosis of necrotising retinitis in vitreous samples from patients from the Hospital São Geraldo, Universidade Federal de Minas Gerais, Brazil. The vitreous samples were collected by paracentesis and stored until analysis. Samples were analysed by PCR using specific primers designed to amplify herpes simplex virus 1 (HSV-1), varicella zoster virus (VZV), or human cytomegalovirus (HCMV). In a case of anterior uveitis, PCR was performed with a sample from the anterior chamber. Results—Herpesvirus DNA was amplified in 11 of 17 samples. HCVM DNA was detected in nine samples but DNA from HSV-1 and VZV were detected only once each. Conclusion—These results strongly suggest that PCR could be used for a rapid complementary diagnosis of viral uveitis and retinitis. A prospective study to evaluate the PCR results, clinical evolution, and treatment is imperative to corroborate the real value of PCR in diagnosis and how it could help the clinicians' approach. Key Words: polymerase chain reaction • uveitis • retinitis